Strengthening communication skills: reading and writing, through the analysis of traditional Vallenato songs with fifth-grade students - Britto Jiménez, Gina Katherine; Villalba Contreras, Virginia Esther; Bovea Ramos, Álvaro Enrique (Revista UNIMAR, 2023)
The strengthening of communication skills allows us to function in daily life. Therefore, the objective of this research was to strengthen reading and writing skills, through the analysis of traditional Vallenato songs, with fifth-grade students. Methodologically, the study was framed in the critical paradigm, under the qualitative approach, with the pedagogical action research method, energized in three phases: deconstruction, reconstruction, and evaluation of the reconstructed practice. 33 students made up the work unit. The instruments were: a questionnaire addressed to teachers and an observation log. The results of the diagnosis evidenced the difficulty of the students in the development of the aforementioned skills. With the implementation of the workshops, they expanded their vocabulary, expressing themselves with solid arguments and writing pertinent summaries. This allows us to conclude that traditional Vallenato songs strengthened communication skills; in addition, the students were able to interpret the message that the composer embodied in the songs.